Protistan Communities Within the Galápagos Archipelago With an Emphasis on Micrograzers - Jang, Se Hyeon; Lim, Prisca; Torano, Olivia; Neave, Erika F.; Seim, Harvey; Marchetti, Adrian (Frontiers in Marine Science, 2022)
The Galápagos Archipelago is a globally significant biodiversity hotspot. However, compared to the relatively well-known megafauna, the distribution and ecological significance of marine protists in this system are poorly understood. To gain an understanding of the protistan assemblages across trophic modes, an intensive oceanographic survey was conducted in the Galápagos Marine Reserve (GMR) in October of 2018. The Equatorial Undercurrent (EUC)-influenced region had higher chlorophyll-a (Chl-a) concentrations than those of the eastern regions of the archipelago, along with higher abundances of protistan grazers. Specifically, proportions of autotrophic and potentially mixotrophic dinoflagellates were higher in the EUC, whereas in the eastern regions, heterotrophic dinoflagellates and chlorophytes dominated. Taxonomic composition and biochemical indicators suggested proportions of micrograzers and their associated heterotrophic biomass was higher in the oligotrophic, low Chl-a regions in the east. We also report observations from a dinoflagellate bloom in the western archipelago, which was heavily influenced by upwelling of the EUC. The red tide-forming dinoflagellate Scrippsiella lachrymosa was highly detected through light microscopy and DNA amplicon sequencing. In addition, the heterotrophic dinoflagellate Polykrikos kofoidii was detected and based on cell densities, was estimated to graze up to 62% of the Scrippsiella bloom population per day, likely hindering bloom propagation. Our findings provide new insights on the importance of micrograzers structuring protistan communities in the Galápagos Archipelago.